Numerical Simulation of the Dynamic Responses and Impact-Bearing Capacity of CFDST Columns under Lateral Impact - Jin-Long Guo; Shuang Pan; Xiao Guo; Zheng-Yu Wu (Buildings, 2023)
The concrete-filled double steel tube (CFDST) has been more and more widely used in infrastructure due to its greater moment of inertia compared to the ordinary concrete-filled steel tube (CFST). With the increase in collision accidents occurring in recent years, the research on CFDST under impact needs more attention. To study the dynamic responses of CFDST columns under lateral impact, the finite element package ABAQUS was used to simulate the impact force and mid-span deflection of the column under the coupling action of axial force and lateral impact based on the comparison of experimental data in the literature. The influence of hollow ratio, axial compression ratio, slenderness ratio, impact energy, and material strength on the dynamic responses of the CFDST column are studied. The results show that with the increase in the hollow ratio from 0.3 to 0.8, the residual mid-span deflection of the CFDST column decreases by 77.9%. The mid-span deflection shows an increasing trend following a decreasing one with the axial compression ratio increasing. With the increase in the slenderness ratio from 30 to 60, the plateau impact force decreases by 62.5%, and the residual mid-span deflection increases by 240.5%. The practical formulas for the impact-bearing capacity and residual mid-span deflection of the CFDST column are suggested with high accuracy.